Noncovalent chalcogen and tetrel bonding interactions: Spectroscopic study of halide–carbonyl sulfide complexes. Issue 2 (6th February 2023) - Haakansson, Christian T.; Watson, Peter D.; Corkish, Timothy R.; Robinson, Hayden T.; McKinley, Allan J.; Wild, Duncan A.
Abstract: Chalcogen and tetrel intermolecular bonding interactions formed between carbonyl sulfide and halide anions have been studied utilizing a combined experimental and theoretical approach. In particular, high‐level CCSD(T) energetics and experimental anion photoelectron spectroscopy have been used in order to assign the dominant binding motif exhibited in these complexes. Halide anions solvated by multiple carbonyl sulfide molecules have also been investigated in order to ascertain the effect that additional binding partners has on the strength of the noncovalent interactions. The experimental and computational results support the main binding motif of carbonyl sulfide molecules with halide anions being chalcogen bonding, both in dimer complexes and larger solvated complexes. In addition, comparison between the noncovalent interactions formed by halides with carbon disulfide, carbonyl sulfide, and carbon dioxide allows a deeper understanding of noncovalent binding strength in relation to isoelectronic species. Key points: Spectroscopic and ab initio characterization of halide–carbonyl sulfide van der Waals complexes bound through chalcogen and tetrel bonding. Detailed insight into chalcogen and tetrel bond strength in the context of changing chemical environments. Effect of increasing solvation on noncovalent binding strength. Abstract :